Drgania Uderzeniowe Prętów - Cempel, C. (Engineering Transactions, 1970)
In this paper are examined free impact vibrations of rods. In calculation, perfect elastical percussion of the section of the rod with rigid stop is assumed. Next, by means of the adaptation of the solutions method the dependence of the frequency of free impact vibration on the percussion parameters of the rod is obtained. Further, the displacement and velocity from of vibrations of the rod are given.